2020
DOI: 10.1177/0269216320929538
|View full text |Cite
|
Sign up to set email alerts
|

Building organizational compassion among teams delivering end-of-life care in the intensive care unit: The 3 Wishes Project

Abstract: Background: The 3 Wishes Project is a semistructured program that improves the quality of care for patients dying in the intensive care unit by eliciting and implementing wishes. This simple intervention honors the legacy of patients and eases family grief, forging human connections between family members and clinicians. Aim: To examine how the 3 Wishes Project enables collective patterns of compassion between patients, families, clinicians, and managerial leaders in the intensive care unit. Design: Using a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 61 publications
0
24
0
2
Order By: Relevance
“…The 3 Wishes Project is an EOL intervention aimed to honour dying patients and support families in grief. It has grown into a programme of research aimed at improving EOL care across critical and acute care settings 28–30. Many studies have emerged from the larger multicentre research programme,28–30 demonstrating feasibility, scalability, transferability and value.…”
Section: Methodsmentioning
confidence: 99%
“…The 3 Wishes Project is an EOL intervention aimed to honour dying patients and support families in grief. It has grown into a programme of research aimed at improving EOL care across critical and acute care settings 28–30. Many studies have emerged from the larger multicentre research programme,28–30 demonstrating feasibility, scalability, transferability and value.…”
Section: Methodsmentioning
confidence: 99%
“…We were unable to abstract and thus evaluate the effect of hospital census and the need for transfers on pandemic EOL care. Because prior studies have demonstrated many positive influences of the 3WP ( 13 15 ), we did not evaluate its effect on families during this study period, acknowledging the possibility that the 3WP was particularly valuable due to the tragic circumstances of the pandemic. The ability to provide compassionate care can help alleviate HCWs’ distress and enhance interpersonal connections during these unprecedented times ( 41 , 43 , 44 ) although this was not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Close communication between families of acutely ill patients has been shown to improve psychological outcomes and lead to higher quality surrogate decision making surrounding the direction of care. 39,40 Electronic communication through phone calls or video conferencing was widely adopted by health care systems during the COVID-19 pandemic. 28 A study that evaluated the feasibility and acceptability of electronic communication for palliative care family meetings found that 80% of family members felt comfortable articulating questions and expressing thoughts throughout the meeting.…”
Section: Connecting With the Health Care Teammentioning
confidence: 99%